Commonwealth Caribbean employment and labour law - Corthésy, Natalie; Harris-Roper, Carla-Anne (Commonwealth Caribbean law series, 2014)
"This new edition to the series will provide an up-to-date textbook covering a wide-range of employment and labour law issues which affect the Commonwealth Caribbean. Initially the book will embark on a comparative analysis of employment and labour law in Jamaica, Trinidad and Barbados, as a reference point for distinguishing the laws of other Commonwealth Caribbean jurisdictions. The book will continue to examine how the law operates within the legal systems of the Caribbean, taking into account the umbilical link to British jurisprudence and the persuasive precedent of other Commonwealth jurisdictions, and the impact this has had on the growth and development of the area. Commonwealth Caribbean Employment and Labour Law will be essential reading for students enrolled on Employment Law, Discrimination and Dismissal Law courses in the Caribbean"--